Los orígenes de la vulnerabilidad macroeconómica y sus principales efectos: propuesta de un marco teórico - Luis Hernando Portillo-Riascos (Revista Iberoamericana de Estudios de Desarrollo)
The objective of this study is present a systematical proposal that allows to understand the concept of macroeconomic vulnerability (MV), the sources that generate and the mechanisms through which it transmits its effects toward the main macroeconomic aggregates; particularly, in the developing economies. Like this, in contrast to other studies that have focused on the effects that generate the external shocks on financial markets, within of this research what is sought is deep into the caused impact by them from the perspective of the real economy. Inside this exercise, it systematized the main contributions from of Neoestructuralism, where, although there isn’t formal proposal of MV, it was found that there are a number of elements from which a framework of analysis can be configured that allows to understand the economic dynamic of this type of countries.